LabEAD AutoTest: Online Tests of Hardware Designs - Hayashi, Victor T.; Ruggiero, Wilson V.; Almeida, Felipe V. de (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2022: Anais Estendidos do XXII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg_estendido.2022.227007, 2022)
The outsourcing of hardware production to third-party foundries (often overseas) for cost reduction presents additional challenges to the security of hardware devices. If Hardware Trojans are added to hardware devices during the fabrication phase, design-time approaches are not enough. LabEAD AutoTest is an open-source tool useful to perform automated tests in a hardware design in runtime. It is based on the MQTT protocol, the remote lab LabEAD and Python Notebook. An example of a glitch in an adder described in the VHDL Hardware Description Language was used to show the soundness of the proposed tool. LabEAD AutoTest may be useful to aid in the hardware device validation process.